Moving from Paper-Based Testing (PBT) to Computer-Based Testing (CBT) for Classroom Use: Exploring the Opportunities and Challenges - Ferdiansyah, Sandi (Sebelas Maret University, 2016)
From educational perspectives, the ability of teachers to design a computer-based test material is believed to become a critical element to develop a breakthrough particularly in educational assessment practices in this twenty first century era. In addition, the ability of the teachers to create the digital testing is also expected to revitalize the implementation of testing for educational purposes. Though technology mediated testing provides teachers with such huge opportunities, its application remains static since the shift from traditional mode of testing to computerized testing is absolutely challenging. To back up those compelling arguments, this paper attempts to discuss four tangible opportunities for teachers to self-create computer-based testing for classroom use such as 1) teacher-student engagement in virtual learning environment; 2) testing efficiency and practicality; 3) interactive exercise for measurement; and 4) maintenance of high level of scoring accuracy. The paper will also talk about the challenges the teachers might face while creating and implementing the e-testing, namely 1) affordance of technological tools; 2) teacher-student familiarity in computer mediated learning and testing; and 3) innovation in adamant teaching and learning situation. At the end of this chapter, brief guidelines on how to administer and implement CBT for classroom use are proposed. The significance of this chapter is finally addressed to the needs of capacity building of e-testing construction and implementation for educational purposes. Consequently, there is an expectation of growing awareness of the teachers and practitioners towards the current paradigm in teachers-made test using computer in the context of classroom settings and beyond.